2019
DOI: 10.1093/annonc/mdy507
|View full text |Cite
|
Sign up to set email alerts
|

Immune biomarkers of response to immune-checkpoint inhibitors in head and neck squamous cell carcinoma

Abstract: Anti-programmed cell death protein 1 (PD-1) agents have become the standard of care for platinum-refractory recurrent/metastatic head and neck squamous cell carcinoma (HNSCC) and are currently being evaluated in various disease settings. However, despite the gain in overall survival seen in some of the clinical trials, the majority of patients display primary resistance and do not benefit from these agents. Taking into consideration the potentially severe immune-related toxicities and their high cost, the sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
174
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(179 citation statements)
references
References 136 publications
(212 reference statements)
4
174
1
Order By: Relevance
“…Additionally, we also observed a positive association between the number of expressed CT genes with different types of immune cells. Recently, there is accumulating evidence confirming the association between immune biomarkers and the response to anti‐PD‐1/L1 therapy across several solid tumors . In this study, we found that PD‐1 / PD‐L1 expression was positively correlated with the number of expressed CT genes, suggesting that CT genes represent a potential marker for effective PD‐1/L1 immunotherapy.…”
Section: Discussionsupporting
confidence: 64%
“…Additionally, we also observed a positive association between the number of expressed CT genes with different types of immune cells. Recently, there is accumulating evidence confirming the association between immune biomarkers and the response to anti‐PD‐1/L1 therapy across several solid tumors . In this study, we found that PD‐1 / PD‐L1 expression was positively correlated with the number of expressed CT genes, suggesting that CT genes represent a potential marker for effective PD‐1/L1 immunotherapy.…”
Section: Discussionsupporting
confidence: 64%
“…Given the small number of patients with uterine cervical cancer for whom HPV status could be determined (12 of 20 patients), it is difficult to evaluate the relationship between HPV status and response to nivolumab in the current study. Studies investigating the relationship between HPV status and response to nivolumab have had mixed results …”
Section: Discussionmentioning
confidence: 99%
“…Ten members are included in the B7/CD28 family, including B7-1/CD28, B7-2/cytotoxic T lymphocyte antigen 4 (CTLA-4), ICOS-L/ICOS and programmed cell death 1 (PD-1)/PD-1 ligand (PD-L1). 8,9 Inhibitors of PD-L1/PD-1 have been approved by Food and Drug Administration (FDA) as second-line treatments for lung cancer, because of their therapeutic benefit in clinical trials. 6,7 The B7/CD28 family regulates the proliferation and function of T cells as antigen-presenting cells (APCs).…”
Section: Introductionmentioning
confidence: 99%
“…(range:[1][2][3][4][5][6][7][8][9][10][11][12]. The median score was used to determine the cut-off value of low or high CD28H expression.…”
mentioning
confidence: 99%